Space and technique. Space, spatiality, spatialisation - Montani, Pietro (E|C, 2021)
Moving from a phenomenological and "embodied" approach to the issue of space, this article discusses its properties with particular reference to "technical reliance" which characterizes, in an original way, the behaviors of mankind. The purpose of the discussion is to differentiate spatial experiences endowed with plasticity from those in which technical reliance proceeds to a reduction, which can be massive, of the sensitive qualities of the world-environment. In this way, an urgent critical task specifically aimed at semiotic analysis is envisaged: that of inspecting and adequately describing the areas of intersection between cyberspace and real space.